Intrahousehold gender relations and sustainable farming: Survey evidence from four African countries - Ragasa, Catherine; Lambrecht, Isabel B.; Cole, Steven; Ma, Ning (International Food Policy Research Institute, 2025)
Inconsistency in self-reported intra-household decision making: -Merely enumeration errors? -Intra-household power relations (Ambler et al. 2021; Annan et al. 2021) Asymmetry in power and subjective perceptions: -Intra-spousal communications -Agreement: Less Intra-household friction -> faster decision-making and speedy actions -Disagreement: Underlying conflict and slower joint evaluation of options Disagreement -> Poorer development outcomes: -Reproductive health care use (Story and Burgard, 2012) -Children’s well-being (Annan et al., 2021), Women’s well-being (Ambler et al., 2021) -Agricultural outcomes? Limited study Contributions of our study: -Describe and compare spousal decision-making perceptions across countries -Explore the factors explaining disagreement -Association of spousal (dis)agreement on decision-making roles and agricultural outcomes